k-trees, k-ctrees and Line Splitting Graphs - Mathad, Veena; Basavanagoud, B. (International Journal of Applied Mathematical Research, 2012)
Let G = (V,E) be a graph. For each edge ei of G, a new vertexe?i is taken and the resulting set of vertices is denoted by E1(G). Theline splitting graph Ls(G) of a graph G is defined as the graph havingvertex set E(G)SE1(G) with two vertices adjacent if they correspondto adjacent edges of G or one corresponds to an element e?i of E1(G)and the other to an element ej of E(G) where ej is in N(ei). In thispaper we characterize graphs whose line splitting graphs are k ? treesand k ? ctrees.